20+ Years and alive with primary myelofibrosis: Phenotypic signature of very long‐lived patients. Issue 3 (5th December 2018) - Penna, Domenico; Lasho, Terra L.; Finke, Christy M.; Vallapureddy, Rangit R.; Hanson, Curtis A.; Ketterling, Rhett P.; Pardanani, Animesh; Gangat, Naseema; Tefferi, Ayalew
Abstract: In the last decade, several prognostic models for primary myelofibrosis (PMF) have been introduced and shown to be effective in predicting overall survival. The main objective for this study was to identify clinical and genetic markers of very long (20+ years) survival in PMF. A total of 1282 patients with PMF were considered (median age 65 years, range 19‐92; 63% males); 26 (2%) patients (median age 51 years, range 28‐71; 38% males) survived their disease for at least 20 years (long‐lived patients) and 626 (49%) patients (median age 68 years, range 27‐92; 66% males) died within 5 years of their diagnosis (short‐lived patients). Multivariable logistic regression analysis identified 7 variables that were associated with survival beyond 20 years: age ≤ 70 years ( P = .002); female sex ( P = .03); hemoglobin level ≥ 10 g/dL for women and ≥ 11 g/dL for men ( P = .03), leukocyte count ≤25 × 10 9 /L ( P = .009), platelet count ≥100 × 10 9 /L ( P = .002), circulating blasts <2% ( P = .03) and absence of constitutional symptoms ( P = .04). Five‐year mortality was independently predicted by high‐molecular risk mutations ( P < .001); unfavorable or very high risk karyotype ( P < .001); absence of type 1/like CALR mutation ( P < .001); age > 70 years ( P < .001); constitutional symptoms ( P < .001); hemoglobin level < 10 g/dL for women and < 11 g/dL for men ( P < .001); leukocyte count >25 × 10 9 /L ( P = .004); and circulating blasts ≥2% ( P = .001). This study suggests that genetic risk factors in PMF are associated with early mortality while survival beyond 20 years could be predicted by easily accessible clinical variables, including age, sex, blood counts, and symptoms.